O051 Incidence and management of axillary lymphadenopathy post COVID-19 vaccination in a symptomatic breast unit. (22nd July 2022) - Giblin, K; Balasubramanian, I; Downey, E; Butt, A; Allen, M; Power, C; Hill, AK
Abstract: Introduction: Following the mass rollout of COVID-19 vaccination, regional lymphadenopathy presents as a diagnostic dilemma for clinicians. The aim of this study explores the incidence and management of unilateral axillary lymphadenopathy following vaccination at a symptomatic tertiary breast unit. Methods: This is a retrospective review of a prospectively maintained database of all patients who underwent axillary imaging for symptomatic or incidental axillary lymphadenopathy detected on imaging following COVID-19 vaccination between January 2021 – December 2021. Radiological and histological information were obtained from the hospital s NIMIS radiology and PIPE histology system. Additional patient and clinical information was obtained from patient's clinical notes. Results: A total of 253 patients underwent axillary ultrasounds during the twelve-month interval. Of these 24 (9.4%) of patients underwent investigation for axillary lymphadenopathy related to recent COVID vaccination. Of these, 21 patients had image consistent reactive nodes while the remaining 3 patients had normal radiological investigation. Only 6 patients underwent ultrasound guided biopsy of these nodes which confirmed reactive notes. Conclusion: Patient and clinician education is required to raise awareness in COVID-19 related axillary lymphadenopathy. Standardization in the management including the timing of breast screening and radiological investigation in relation to COVID vaccination is required, in order to minimize over investigation in this patient cohort. Take-home message: COVID-19 vaccine related axillary lymphadenopathy is being seen in tertiary symptomatic breast clinic. Patient and clinician education is necessary to raise awareness of this and contribute to a standardised approach of investigation and management of this phenomenon.